In Whose Eyes : The Memoir of a Vietnamese Filmmaker in War and Peace - Trần, Văn Thủy (Film director) (Book collections on Project MUSE., 2016)
"Trần Văn Thủy is a celebrated Vietnamese filmmaker of more than twenty award-winning documentaries. A North Vietnamese Army cameraman during the Vietnam War, he went on to achieve international fame as the director of films that address the human costs of the war and its aftermath. Thuy's memoir, when published in Vietnam in 2013, immediately sold out. In this translation, English-language readers are now able to learn in rich detail about the life and work of this preeminent artist. Written in a gentle and charming style, the memoir is filled with reflections on war, peace, history, freedom of expression, and filmmaking. Thuy also offers a firsthand account of the war in Vietnam and its aftermath from a Vietnamese perspective, adding a dimension rarely encountered in English-language literature"--